O ensino de história: a sala de aula como espaço de produção histórica - Franco, Denize de Azevedo (1992)
The objective of this Dissertation is to present and to discuss the teaching of History inside the classroom, through the didactic books and the contents of the curricula of Rio de Janeiro’s elementary and the contents of the curricula of Rio de Janeiro’s elementary and high schools, in a time – the 70’s and the 80’s – characterized as being of pedagogical and sociopolitical transition. The main intervention of this work is to emphasize the importance of the classroom as an effort to be lived with creativeness. Our main hypothesis of work comprehends matters of methodology in History, for it attempts to promote the student’s historical production as a possibility os rescueing their citizenship. It also presents a comparative picture of the theorical-methodologic orientation which, by influencing new views and demonstrating preoccupation about practices and knowledges, are of fundamental importance. It reports a pedagogical experience, of elaboration of bibliographic and historical documentary material, developed together with the students of the schools of the Rio de Janeiro Municipality. We have used in the elaboration of this Dissertation produced by its author, by students, and by selected bibliography.